Charge dependent adsorption of carbon dioxide on fullerenes. (August 2015) - Ralser, Stefan; Kaiser, Alexander; Probst, Michael; Postler, Johannes; Renzler, Michael; Bohme, Diethard K; Scheier, Paul
Synopsis: A positive surface charge on a buckminsterfullerene leads to an enhanced first shell adsorption capacity of carbon dioxide in comparison to neutral or negatively charged species. The surface acts like a sponge that can adsorb and release carbon dioxide in a controllable manner.